Corpus christi eaudiobook Stories. - Johnston, Bret Anthony (Recorded Books Inc., 2005)
Called a "rising star" by Publishers Weekly, Bret Anthony Johnston has won the James Michener Fellowship and the Christopher Isherwood Prize. His writing has been featured in The Paris Review and in many anthologies, including New Stories from the South: The Year's Best, 2004 (SV017). Corpus Christi was named a Best Book of the Year by London's The Independent. Fans of Raymond Carver will enjoy this collection of lean, evocative tales of tragedy and hope, each set in the small Texas city on the gulf.